c-erbB-2 oncoprotein in screen-detected breast carcinoma: an immunohistological study. - Soomro, S; Taylor, P; Shepard, H; Feldmann, M; Sinnett, H; Shousha, S (1993)
This study was aimed at comparing screen-detected and symptomatic breast carcinomas with regard to the prevalence of positive immunostaining for c-erb-B-2 oncoprotein. Paraffin sections of 81 breast carcinomas detected through the National Screening Programme were examined for the over-expression of c-erbB-2 oncoprotein using the avidin-biotin immunoperoxidase technique and 2 different specific antibodies: 21N and 4D5. Twenty-one other carcinomas detected in symptomatic patients were similarly examined for comparison. The screen-detected lesions were of 2 types: palpable and impalpable which required needle localization prior to surgical removal. Of the 81 screen-detected tumours, only 8 were c-erbB-2 positive, compared with 5 out of 21 non-screen-detected tumours. When only invasive carcinomas were considered, 5 out of 63 screen-detected cases were positive, compared with 5 out of 15 symptomatic cases. Four out of the 5 screen-detected positive invasive carcinomas were clinically palpable. Our results show an obvious trend towards a lower prevalence of c-erbB-2 oncoprotein over-expression in screen-detected carcinomas. As this over-expression is thought to be associated with increased tumour aggressiveness, the findings suggest a low prevalence of aggressive tumours in screen-detected lesions, particularly impalpable invasive carcinomas, identified so far.